Analysis and Damping Control of Power System Low-frequency Oscillations - Wang, Haifeng; Du, Wenjuan (Power Electronics and Power Systems, 2016)
This book presents the research and development results on power systems oscillations in three categories of analytical methods. First is damping torque analysis which was proposed in 1960's, further developed between 1980-1990, and widely used in industry. Second is modal analysis which developed between the 1980's and 1990's as the most powerful method. Finally the linearized equal-area criterion analysis that is proposed and developed recently. The book covers three main types of controllers: Power System Stabilizer (PSS), FACTS (Flexible AC Transmission Systems) stabilizer, and ESS (Energy Storage Systems) stabilizer. The book provides a systematic and detailed introduction on the subject as the reference for industry applications and academic research.